2014
DOI: 10.1371/journal.pone.0096905
|View full text |Cite
|
Sign up to set email alerts
|

Role of Omega-3 Fatty Acids in the Treatment of Depressive Disorders: A Comprehensive Meta-Analysis of Randomized Clinical Trials

Abstract: BackgroundDespite omega-3 polyunsaturated fatty acids (PUFA) supplementation in depressed patients have been suggested to improve depressive symptomatology, previous findings are not univocal.ObjectivesTo conduct an updated meta-analysis of randomized controlled trials (RCTs) of omega-3 PUFA treatment of depressive disorders, taking into account the clinical differences among patients included in the studies.MethodsA search on MEDLINE, EMBASE, PsycInfo, and the Cochrane Database of RCTs using omega-3 PUFA on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
308
8
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(339 citation statements)
references
References 121 publications
9
308
8
14
Order By: Relevance
“…Ancillary treatments such as adjunctive eicosapentaenoic acid (EPA) (level 2),169, 279, 280 N ‐acetylcysteine (level 3),281 and light therapy (level 3),282 including bright light delivered midday (level 3),283 are also recommended as third‐line treatment options to use adjunctively to other medications. There may be additional benefits to using light therapy in combination with total sleep deprivation (level 2), although there is little clinical experience with this technique.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…Ancillary treatments such as adjunctive eicosapentaenoic acid (EPA) (level 2),169, 279, 280 N ‐acetylcysteine (level 3),281 and light therapy (level 3),282 including bright light delivered midday (level 3),283 are also recommended as third‐line treatment options to use adjunctively to other medications. There may be additional benefits to using light therapy in combination with total sleep deprivation (level 2), although there is little clinical experience with this technique.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…The antidepressant efficacy of omega-3 PUFAs on adults with major depressive disorder has been confirmed in several recent meta-analyses (Grosso et al, 2014b;Sublette et al, 2011). However, results are inconsistent and seem to be influenced by the preparation and dosage used (Bloch and Hannestad, 2012).…”
Section: Omega 3 Polyunsaturated Fatty Acids and Depressionmentioning
confidence: 91%
“…In particular, natural supplements such as St John's wort (Linde et al, 2005), S-adenosylmethionine (SAMe) (Papakostas, 2009), omega 3 polyunsaturated fatty acids (PUFAs) (Grosso et al, 2014b;Sublette et al, 2011) and zinc (Lai et al, 2012) have antidepressant benefits in adults. Investigations on the antidepressant effects of nutritional and herbal treatments for paediatric depression are less common, although have the potential to build upon current treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of clinical trials of treatment with LCn3PUFAs for depression concluded that the use of these supplements is effective in patients with a diagnosis of Major Depressive Disorders (MDD) and in depressive patients without a diagnosis of MDD. [33] This study investigated associations of LCn3PUFA status, with (a) depression severity and (b) angina symptoms in patients with cardiac disease and depression who were low fish consumers. It was hypothesised that in patients with heart disease, LCn3PUFA status would be inversely associated with depression severity and angina symptoms.…”
Section: Introductionmentioning
confidence: 99%